Primary Hospital Management of Snakebites in Morona Santiago, Ecuador: A Clinical-Epidemiological Study - Arízaga Pino, María Daniela; Robles Pérez, Jessica Cecilia; Karina Noemí; Escudero Vallejo, Julio Santiago; Ochoa Andrade, Miguel Jacob (Revista Cubana de Medicina Tropical, 2025)
Introduction: Snakebites in Ecuador mainly affect isolated low-income rural communities, leading to delayed treatment and underreporting of cases. Objective: This study aimed to determine the clinical-epidemiological characteristics of snakebites attended in a primary hospital in Morona Santiago, Ecuador. Methods: A descriptive study analyzed 66 cases reported as "Toxic effect of snake venom" (code T63.0) according to the International Classification of Diseases (ICD-10). Patient medical records were obtained from the hospital's Electronic Health Record system. Descriptive statistics were calculated for variables on the sociodemographic characteristics of patients, seasonality, diagnosis, and treatment of snakebites. Results: Snake bites were more common in men (57.58%) and adults (63.64%). The Shuar indigenous population was the most affected (63.64%). The prevalence of snake bites peaked in the first half of the year, particularly in January, February, and April. Bothrocophias microphthalmus and Bothrops atrox species represented 75.76% of cases. Most cases were mild (59.09%) and lacked complications (71.21%). The mean time from the bite to the administration of antiophidic serum was 3.12 hours (SD ± 3.98 hours; range: 0.25-27.50 hours). Conclusions: Snakebites significantly impact indigenous communities in Ecuador with limited healthcare access. Addressing delayed treatment and underreporting cases requires improving rural healthcare accessibility and educating patients and professionals. Local studies are the first step to understanding local reality and adapting the national guidelines to its context.